Fernandão : a complexidade na morte do ídolo e a construção do mito - Provenzano, Bruna Atti (2017)
In this study, our gaze turns to the relationship between the media and the death of football players. Our focus is on the journalistic coverage of the Fernandão death. We delimit, as the essence of our analysis, articles published by Correio do Povo e Zero Hora. We limit our corpus with five piece of news from each journal. They are the first productions of informative sort produced on the idol death and published in the printed version of the newspapers. Our objective is to study the production of meaning in the coverage of the death of a sports idol as Fernandão. We are also motivated by the search for an understanding of the way the piece of news collaborate in the construction of the athlete myth.We will proceed using the analysis method as the Paradigm of Complexity from Edgar Morin (2011), which bets not on the linearity of the way, but on the constant dialogue between different knowledge. We define the analysis technique of our corpus the Semiology from Roland Barthes (1996). By unveiling the speeches - verbal and nonverbal - we seek to find what is obtuse in the productions about the Fernandão death. By unveiling the speeches - verbal and nonverbal - we seek to find what is obtuse in the productions about the Fernandão death. Our analyzes will be guided by six categories a priori that we understand as pertinent for the accomplishment of this study. Our starting point is based on: Photography, with the subcategories studium and punctum; Fait divers; myth; imaginary; Stereotype and socioleto. All are based on Barthes‘ reflections.The study revealed similarities in the discourse produced by the two journals about the death of Fernandão. From verbal and non-verbal elements, the material tries to clear the player’s trajectory, highlighting, above all, the moments of victory and joy, suppressing the contradictions.